Na marginesie artykułu Wojciecha Włodarczyka „Rok 1989 – wokół pojęcia modernizmu” - Turowski, Andrzej (Artium Quaestiones, 2019)
Na marginesie artykułu Wojciecha Włodarczyka „Rok 1989 – wokół pojęcia modernizmu”